'The Clach': Alexander Mackenzie and the Land Question in the Late-Nineteenth Century Highlands and Islands. Issue 1 (May 2017) - Thomas, Ben
Abstract : This article uses the career and writings of the Highland land reformer Alexander Mackenzie, to shed new light on the evolution of Highland land reform in the years leading up to the Crofters' Act of 1886. Mackenzie's output as a writer and journalist shows that his early experiences of living and working on the land are vital to understanding his approach to the land question, and led him to focus not on abstract or ideal principles but on building popular consensus to secure the most pressing reforms. This moderate and pragmatic approach was not universally popular though, especially among Mackenzie's more radical reformist contemporaries. The tensions these disagreements created are symptomatic of the problems that beset the 'Crofting Community' in the 1880s and '90s: problems that would eventually cause the land reform movement to split. Nevertheless, Mackenzie's influence on the Crofters' War was huge, and deserves greater scholarly recognition.